Investigating the risk factors associated with pedestrian injury severity in Illinois. (June 2016) - Pour-Rouholamin, Mahdi; Zhou, Huaguo
Abstract: Introduction: Pedestrians are known as the most vulnerable road users, which means their needs and safety require specific attention in strategic plans. Given the fact that pedestrians are more prone to higher injury severity levels compared to other road users, this study aims to investigate the risk factors associated with various levels of injury severity that pedestrians experience in Illinois. Method: Ordered-response models are used to analyze single-vehicle, single-pedestrian crash data from 2010 to 2013 in Illinois. As a measure of net change in the effect of significant variables, average direct pseudo-elasticities are calculated that can be further used to prioritize safety countermeasures. A model comparison using AIC and BIC is also provided to compare the performance of the studied ordered-response models. Results: The results recognized many variables associated with severe injuries: older pedestrians (more than 65 years old), pedestrians not wearing contrasting clothing, adult drivers (16–24), drunk drivers, time of day (20:00 to 05:00), divided highways, multilane highways, darkness, and heavy vehicles. On the other hand, crossing the street at crosswalks, older drivers (more than 65 years old), urban areas, and presence of traffic control devices (signal and sign) are associated with decreased probability of severe injuries. Conclusions and practical applications: The comparison between three proposed ordered-response models shows that the partial proportional odds (PPO) model outperforms the conventional ordered (proportional odds—PO) model and generalized ordered logit model (GOLM). Based on the findings, stricter rules to address DUI driving is suggested. Educational programs need to focus on older pedestrians given the increasing number of older people in Illinois in the upcoming years. Pedestrians should be educated to use pedestrian crosswalks and contrasting clothing at night. In terms of engineering countermeasures, installation of crosswalks where pedestrian activity is high seems a promising practice. Highlights: We examined the confounding factors that affect the injury severity of pedestrians in single-vehicle, single-pedestrian cashes in Illinois considering the ordered nature of severity. Factors like older pedestrians, not wearing contrasting clothing, adult drivers, drunk drivers, and darkness increase injury severity. Factors like crossing the street at crosswalks, older drivers, urban areas, and presence of traffic control devices decrease injury severity. Three different ordered-response models were compared in terms of performance. Partial proportional odds model was found to outperform the other ordered-response models.